Jazz, pressure and self esteem: the insider stories of Malaysian jazz students - Wong, Siao Ern; Chan, Cheong Jan (Faculty of Music and Performing Arts, Universiti Pendidikan Sultan Idris, 2014)
Recent years has witnessed an increasing number of tertiary education level students pursuing jazz performance studies. Jazz is a relatively new musical culture in Malaysia, and little has been documented of the process of a student learning jazz locally. One of the key problems encountered by students is low self-confidence in learning and improvising jazz. This issue is largely connected to the learner’s self-perception and self esteem. Combined with a lack of awareness and understanding of the cultural and musical aspects of jazz, these factors can significantly affect a student’s progress in learning. This paper attempts to provide a look into the insider story—To shed light on the process of Malaysian students learning jazz improvisation. A phenomenological approach will be employed: In-class observations and interviews will be carried out with jazz piano major students enrolled in a local university. The data will be reflected upon and interpreted by discussion. It is hoped that by presenting the inner perspectives of the subjects in their journey of jazz learning, valuable insight can be gained into the area of intercultural pedagogy and learning.